Analisis Kemampuan Representasi Matematis Ditinjau dari Gaya Kognitif Field Dependent dan Field Independent - Hafriani, Hafriani; Hamdani, Humaira; Salasiyah, Cut Intan (Jurnal Ilmiah Pendidikan Matematika Al Qalasadi, 2024)
This study focuses on using different cognitive styles to solve mathematical issues. Their cognitive styles can be observed when students work on mathematical problems involving mathematical representation skills. Furthermore, the analyst should assess the mathematical representation abilities of pupils at MTsN 1 Banda Aceh using the field-dependent (FD) and Field Independent (FI) cognitive styles. A descriptive, qualitative technique is used. This study employs purposive sampling procedures and focuses on two pupils from class VIII-2, one identified as FD and the other as FI. Instruments utilized include representation skill tests, interview guidelines, and GEFT questions. Analyzing the research data involves data reduction, presentation, triangulation, and conclusion formulation. The research findings point to many conclusions: (1) FI students find it easier to understand issues, can provide better conceptual explanations, solve problems faster, and explain their solutions accurately. (2) FD students have more difficulty solving issues because they rely on teacher directions. Additional concerns include their failure to analyze and comprehend information and retain concepts from challenges effectively. It is envisaged that students will understand their cognitive types to improve their mathematical representation skills in math and other courses.